Economic consequences of state failure; Legal capacity, regulatory activity, and market integration in Poland, 1505-1772 - Mikołaj Malinowski (European Historical Economics Society (EHES), 2018)
With use of innovative proxies and new annual data, I demonstrate that relatively high legal capacity and regulatory activity of the early-modern Polish parliament was positively associated with deeper commodity market integration. Conversely, the lack of effective law-making, caused by the right of a single delegate to discontinue the parliamentary sessions, fostered market fragmentation. This indicates that early parliamentary regimes might have required legal capacity to harmonize domestic institutions and reduce the transaction costs. The Polish case suggests a hypothesis that the pre-1800 'Little Divergence' between European parliamentary regimes could potentially be partially explained by differences in their capacities.
Keywords: N43; N73; 330; Legal capacity; market integration; preindustrial economic development; Eastern Europe